The impact of happiness on managers' contextual and task performance - Hosie, Peter; Willemyns, M.; Sevastos, Peter (John Wiley & Sons Ltd., 2012)
The ‘happy–productive worker thesis’ has long intrigued organisational researchers and practitioners. Despite mixed empirical evidence from decades of research, there is support in the literature for this thesis. An account is provided on a variation on the enduring debate of the happiness–productivity theme, to support an emerging ‘happy–performing managers proposition’. An empirical study is presented to establish the dimensions of managers’ job happiness (operationalised as affective wellbeing and intrinsic job satisfaction) associated with contextual and task performance. The emphasis was on investigating an aspect of human behaviour with the potential to enhance managerial performance. These findings inform the broader debate on what determines the job performance of managers.